El ejercicio físico en la tercera edad - Cuenca Díaz, Raisa; Almares Pupo, Madelin; Socorro Cruz, Yudit; Proenza Pupo, Ricardo (Correo Científico Médico, 2012)
<!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se realizó un estudio descriptivo transversal con 35 ancianos del Casa de Abuelos No. 1 del Municipio Holguín. Se estudiaron los procesos degenerativos propios de la tercera edad y la influencia del ejercicio físico para evitar el desarrollo de ciertas enfermedades y prolongar la vida sobre la base de comportamientos saludables. Las enfermedades más comunes fueron la hipertensión arterial y la artritis reumatoidea. El total de los ancianos expresó sentir beneficios físicos y psicológicos con la práctica sistemática de ejercicios. Palabras clave: ejercicio físico, ancianos ABSTRACT A cross-sectional study in 35 elderly patients of number one Nursing Home of Holguín Municipality was performed. The degenerative processes in the elderly were studied as well as the influence of physical exercise to prevent the development of some diseases in order to prolong the patients´ life, based on healthy behaviors. Hypertension and rheumatoid arthritis were the most common diseases. Most of elderly patients expressed to feel a considerable improvement from physical and psychological point of view, before practicing physical exersices systematically. Key words: physical exercises, elderly